Russia's Arctic strategies in the context of the Ukrainian crisis. Issue 1 (2nd January 2017) - Konyshev, Valery; Sergunin, Alexander; Subbotin, Sergei
Abstract: This study aims to examine Moscow's Arctic policies in the wake of the Ukrainian crisis. Particularly, it tries to explain why the Kremlin – in contrast with its strategies in the post-Soviet space – opted for a cooperative model of its behaviour in the High North. Furthermore, this paper discusses the question whether Moscow has radically changed its Arctic strategies in the context of the Ukrainian crisis or its course basically remained the same? Based on the analysis of Russia's principal doctrinal documents, this article explores Moscow's threat perceptions and its strategic priorities in the Arctic. The authors emphasise the inward-, rather than outward-looking nature of Russia's Arctic strategy which focuses on numerous economic, societal, environmental and socio-cultural problems of the Russian North. In fact, Moscow's international strategy in the region is subordinated to its domestic needs. On the other hand, Russia's preoccupation with its internal problems does not preclude the Kremlin from a rather assertive international course when it comes to the protection of Russia's national interests in the Arctic. In this context, the authors analyse Moscow's renewed claim on the expansion of the Russian continental shelf and military modernisation programmes. In sum, the authors believe that Russia is serious about being a responsible and predictable actor who is interested in fostering regional cooperation and strengthening multilateral regimes and institutions in the Arctic.